A national collaborative to spread and scale paramedics providing palliative care in Canada: Breaking down silos is essential to success. (4th March 2021) - Carter, Alexandra J. E.; Arab, Marianne; Cameron, Cheryl; Harrison, Michelle; Pooler, Charlotte; McEwan, Ian; Austin, Michael; Helmer, Jennie; Ozel, Gurkan; Heathcote, Jessica; Reardon, Natalie; Anderson, Elizabeth; et al.
Abstract : A national collaborative has been launched in Canada to spread and scale up the Paramedics Providing Palliative Care model. This builds on the knowledge that paramedics in the 9-1-1 (emergency/unscheduled) and scheduled models of care are both historically and currently asked by the public to provide urgent symptom relief within the context of a palliative approach, and that approximately 40% of dying people visit the emergency department in the last two weeks of life despite 70% wishing to die at home. A model of care including a palliative care clinical practice guideline or protocol, specific training, and a mechanism for sharing of goals of care, has been proven to improve the palliative and end of life experience for patients with palliative care needs and their families. It increases the comfort and confidence of paramedics and has benefits to the broader health system. Meaningful and very broad stakeholder engagement and inter-sectoral collaboration is absolutely essential to the success of this innovative approach to care.